Water Management Practices and Environmental Attitudes of Riparian Communities in Sapangdaku River, Cebu Island, Philippines - Joje Mar Perino Sanchez; Reginald Raymund A. Caturza; Marchee T. Picardal; Judelynn M. Librinca; Ruby L. Armada; Hedeliza A. Pineda; Marnan T. Libres; Ma. Lourdes B. Paloma; Sherry P. Ramayla; Jay P. Picardal (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Understanding the social-ecological dynamics of freshwater ecosystem is critical for effective planning and sustainable use of the resource. The study aimed to determine the socio-demographic profile, anthropogenic activities, water utilization of the residents, and waste disposal practices along the Sapangdaku River. Here, we examined water utilization, waste disposal practices and their corresponding impact to health, and environmental attitudes of riverside dwellers (n=120) in Sapangdaku River by using a standardized social health and environmental attitudes survey, respectively. Results show that while river water is still largely used for bathing and backyard farming, its known function as (a) disposal area of human and animal waste, (b) quarry site for pebbles and sand and (c) laundry area significantly decreased in recent years. Responses revealed that occurrence of very common ailments such as cough, gastroenteric problems and skin problems are partly associated to poor river water quality. In terms of people’s environmental attitude, ecocentrism is both positively correlated to environmental movement activism (r=0.445, p=0.000) and human utilization of nature (r=-0.275, p=0.006), putting prime value on the sustainable use of river water that provides benefit to the community. Similarly, environmental movement activism and human utilization of nature (r=-0.327, p=0.001) indicates willingness to participate in environmental activities, hence supported by their decision not to use their environment unfavorably. These findings suggest that community’s concern for the river water resulted to increased participation in various strategies to better maximize the use of the river for various purposes. However, efficient management and restoration of river quality require a holistic view of the problem.